Universality vs. Cultural Specificity in the Relations Among Emotional Contagion, Emotion Regulation, and Mood State: An Emotion Process Perspective - Kuang, Beibei; Peng, Shenli; Xie, Xiaochun; Hu, Ping (Frontiers in Psychology, 2019)
To investigate the universality and cultural specificity of emotion processing in children from different ethnic groups (Han, Jingpo and Dai), we conducted three questionnaires, including emotional contagion scale, emotion regulation scale and the Chinese mood adjective check list (CMACL), among 1,362 ethnic Han, Dai and Jingpo participants (Mage = 13.78 years). We found emotion regulation (reappraisal and suppression) mediated the relations between emotional contagion and mood state, relation: (1) emotional contagion (positive and negative) increased positive mood state and decreased negative mood state by reappraisal, and (2) Negative contagion finally increased negative mood state by weaken effect of reappraisal and enhance effect of suppression. Importantly, we found both universality and ethnic cultural specificity in the relations among emotional contagion, emotion regulation, and state mood. Firstly, the cultural specificity: (1) For Dai and Jingpo participants, negative contagion positively predicted reappraisal, while Han participants did not; (2) Jingpo participants demonstrated a weaker negative relation between reappraisal and negative mood state, and a stronger positive relation between negative contagion and suppression; and (3) Dai participants was the only ethnic group that showed a negative connection between negative contagion and positive mood state. Secondly, the emotion universality: Three ethnics both showed positive relations between negative contagion and negative mood, between suppression and negative mood; For all of them, positive contagion positively predicted positive mood state, mediated by reappraisal. In this paper, we discuss universal emotion processes and ethnic cultural differences in these emotion processes.